Arbitraje, tutela cautelar e imparcialidad "objetiva" del juzgador: un tema para el debate - Ariano Deho, Eugenia (2013)
This article develops the subject of arbitration with an analytical perspective, explaining the origin, scope. purpose andpotential problems thal couldarise. On the other hand, it explain the origin of arbitration according to the international accepted standards as a national analysis of the situation of the arbitration in order to determine if indeed it is being carried out according to international paramelers. It further explains that it is originated in the commercial field, in order to avoid inappropriate “interference ” of the courts that could compromise the success of arbitration, which is know by nature as a quickl and ejficient resolution fot conflicts. It discusses the extensión to which interim protection operates in arbitration, and how permissible is the freedom in this type of conflict resolution, and the guarantees thal must be respected in all processes, inclttding arbitration.